Tantangan Pendidikan dan Pengajaran Kristen Masa Kini Di Ranah Formal - Windikha Praharani; Irene Claravianty Rombo' Paseno; Indriani Rimman Malino (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
In carrying out teaching, one cannot be separated from various challenges which can become obstacles in the educational process, including in teaching Christianity. This research aims to describe in detail the various challenges experienced in the process of learning about Christianity. This research uses literature studies from various sources, so this writing uses qualitative methods based on descriptive theological and social research. The results of the research show that the challenges of contemporary Christian education and teaching in the formal realm are quality of education, industrial revolution 4.0, pandemic and exclusivism